Influence of Ethnic and Religious Values on Corporate Culture of Small and Medium Enterprises (SME) in Sri Lanka - De Alwis, W. P. G. (My University, 2012)
Many management writers argue that the problems faced by SMEs are due to no corporate culture for SMEs. Although Most of the large organizations manage their business activities in a systematic way; in contrast small and medium scale organizations by nature are very informal and managed on a trial and error method. Large organizations develop a management system to achieve their plans and the system in general is called corporate culture. SMEs too have their own way of doing/managing organizations. By nature of SME’s owner and manger may be same person. Hence the owner manages the business the way he wants. The management system is mainly an outcome of his personal value system. Can anyone consider it as corporate culture? Is it his personal culture? There is a question of existence of a corporate/organization culture within small and medium scale businesses. This is the main focus of this research.